Národní park Chövsgöl a přírodní rezervace Choridol Saridag - Součková, Eva
The Chövsgöl National Park is located in the northwest of Mongolia near the border with Russia. It occupies a transition zone where the central Asian steppes meet the Siberian taiga forest. The article presents a brief overview of native flora and fauna and current environmental issues. Eva Součková.